Migration of Korean Daejonggyo Believers to Manchuria in the Early 20th Century and Their Consciousness of Ancient Territory - Seokmin Yoon; Youngjin Kim; Yi Yang (Religions)
In the late Joseon dynasty, many Koreans crossed the border between Joseon and Qing for survival. They then migrated to Manchuria, in the Qing territory, around Mt. Baekdu. In the late 1900s, Japan seized diplomatic and military control of Korea, and in 1910, Korea was annexed by Japan. Many Koreans then moved to the Manchurian region of China. Religion played an important role in the large Korean community formed in Manchuria after the 1910s. During this period, Korean immigrant communities that were centered on religion were established in Manchuria. Among the many religions, Daejonggyo (大倧敎) places great emphasis on national consciousness, and it was an active component of the anti-Japanese armed independence movement to restore national sovereignty. In particular, Daejonggyo claimed that Dangun (檀君), the founder of the Korean people, came down from heaven, established the first nation of the Korean people on Mt. Baekdu, and governed the surrounding area. Accordingly, Daejonggyo considered the Manchurian region to be the ancient territory of the Korean people. In addition, Daejonggyo presented the concept of the Baedal nation as a Dangun lineage and included not only the Korean people but also various northern ethnic groups, such as the Manchurian people. By doing so, Daejonggyo converged not only the Korean Peninsula and the Joseon nation (minjok, 民族) but also the Manchurian region and various ethnic groups in Manchuria into its own territory and people. Through this, Daejonggyo believers not only secured the legitimacy of residing in Manchuria but also gained the justification to drive out the Japanese and restore the Korean peninsular ancient territory.